Analysis of prostate cancer circulating tumour cells isolated with a novel size-based system. (25th February 2016) - Xu, Lei; Mao, Xueying; Chan, Pui Ying; Shamash, Jonathan; Lu, Yong-Jie
Abstract: Background: Isolation of circulating tumour cells (CTCs) from peripheral blood has the potential to provide a liquid biopsy sample that is far easier than tumour tissue biopsy samples to monitor disease progression and response to therapies. Previous studies have mainly focused on the identification of cytokeratin (CK)+/CD45– CTCs. We aimed to optimise a size-based platform for the isolation of CTCs with both epithelial and mesenchymal properties. Methods: We used blood samples spiked with three cancer cell lines or from 14 patients with prostate cancer to compare Parsortix (Angle, Guildford, UK) with the immunomagnetic bead-based systems IsoFlux (Fluxion Biosciences, San Francisco, CA, USA) and CellSearch (Janssen Diagnostics, Raritan, NJ, USA) for CTC isolation. Four-colour immunofluorescence was applied to identify CK, vimentin, and CD45 expression in Parsortix-harvested cells. Fluorescence in-situ hybridisation analysis of androgen receptor ( AR ) and FBXL4 were performed on the same harvested cells as those used in immunofluorescence analysis. Findings: Capture rates were more than 50% for all three spiked cancer cell lines. With Parsortix, similar numbers of CK+ CTCs were harvested compared with IsoFlux, and significantly more CK+ CTCs than with CellSearch (32·1 [29·1] vs 10·1 [9·3], p=0·04). CK–/vimentin+/CD45– circulating cells (median 6, IQR 0–19) were harvested by Parsortix in ten patient samples. Repeated samples were obtained from six patients before they began second-line hormone therapy or chemotherapy and after one or two treatment cycles. The diseases in two patients progressed with rising prostate-specific antigen (PSA) after second-line hormone therapy (81 to 113 ng/mL and 900 to 965 ng/mL), and the number of both CK+/CD45– (15 to 26 and 6 to 86, respectively) and CK–/vimentin+/CD45– cells increased (0 to 2 and 19 to 59, respectively). In the other four patients on chemothreapy, mean PSA concentration and CK+ CTC numbers decreased (68·9 ng/mL [98·0] to 26·5 [38·4] and 17·3 [14·1] to 2·5 [1·7], respectively), but CK–/vimentin+/CD45– cells increased in three patients (5·3 [6·0] to 13·0 [8·5]). AR amplification and FBXL4 deletion were found in both CK+ CTCs and CK–/vimentin+/CD45– cells. Interpretation: We show that the size-based system, Parsortix, can efficiently harvest both CK+ CTCs and CK–/vimentin+/CD45– cells. Genetic alterations were detected in a proportion of vimentin+/CD45– circulating cells, indicating that Parsortix captures circulating prostate cancer cells under epithelial-to-mesenchymal transition. CK+ CTCs and vimentin+/CD45– circulating cells behave differently in response to chemotherapy. Funding: Orchid, Chinese Scholarship Council.